2014
DOI: 10.1128/aem.03349-13
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Transmission of Potato Virus Y, Pepino Mosaic Virus, and Potato Spindle Tuber Viroid in Water

Abstract: Hydroponic systems and intensive irrigation are used widely in horticulture and thus have the potential for rapid spread of water-transmissible plant pathogens. Numerous plant viruses have been reported to occur in aqueous environments, although information on their survival and transmission is minimal, due mainly to the lack of effective detection methods and to the complexity of the required transmission experiments. We have assessed the role of water as a source of plant infection using three mechanically t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 36 publications
0
49
1
4
Order By: Relevance
“…In contrast, transmission following tomato fruit handling was considered unlikely unless the fruit has been squashed to release its sap (46). However, recent findings by Mehle et al (24) suggested that PSTVd transmission via roots through water-mediated movement is of concern in hydroponic and intensive irrigation systems, with PSTVd infectivity surviving in water for up to 7 weeks. However, recent findings by Mehle et al (24) suggested that PSTVd transmission via roots through water-mediated movement is of concern in hydroponic and intensive irrigation systems, with PSTVd infectivity surviving in water for up to 7 weeks.…”
mentioning
confidence: 99%
“…In contrast, transmission following tomato fruit handling was considered unlikely unless the fruit has been squashed to release its sap (46). However, recent findings by Mehle et al (24) suggested that PSTVd transmission via roots through water-mediated movement is of concern in hydroponic and intensive irrigation systems, with PSTVd infectivity surviving in water for up to 7 weeks. However, recent findings by Mehle et al (24) suggested that PSTVd transmission via roots through water-mediated movement is of concern in hydroponic and intensive irrigation systems, with PSTVd infectivity surviving in water for up to 7 weeks.…”
mentioning
confidence: 99%
“…() (Table ) were used for PSTVd and PepMV detection, respectively, as described by Mehle et al . (). For detection of CLVd, the one‐step RT‐qPCR of Monger et al .…”
Section: Methodsmentioning
confidence: 97%
“…Just one infected plant grown from a single infected tomato seed has the potential to rapidly spread the infection mechanically to neighbouring plants, resulting in a larger outbreak. Recently, it has also been shown that irrigation water can be a path for PepMV and PSTVd transmission between plants (Mehle et al, 2014). Therefore, it is essential to monitor for these pathogens through all of the critical points in tomato production and pathogen transmission pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that bumble bees (Shipp et al 2008), the soil-borne fungus Olpidium virulentus (AlfaroFernández et al 2009) and whiteflies (Noël et al 2014) can function as vectors for PepMV. Seed transmission is likely to play a role in long distance spread (Córdoba-Sellés et al 2007;Hanssen et al 2010), and water was confirmed to be the source of PepMV infection (Schwarz et al 2010;Mehle et al 2014).…”
Section: Introductionmentioning
confidence: 99%